Rebel resource strategies in civil war: Revisiting diamonds in Sierra Leone. (November 2019) - Marks, Zoe
Abstract: In the past decade a wealth of research has examined the relationship between natural resources and violent conflict. Cross-national evidence demonstrates that remote resource endowments and weak economies can increase the likelihood of civil war, yet relatively little is known about how armed groups actually extract, manage, and utilize mineral revenues inside a warzone. Drawing on extensive fieldwork with a paradigmatic "resource rebellion" – the former Revolutionary United Front of Sierra Leone – this paper identifies six key strategies and tactics armed groups can employ to manage resource wealth: resource rhetoric; destruction; looting; extraction/production; mortgaging; and taxation. Disaggregating these strategies reveals how the dynamic conflict context determines rebel resource strategies, which change over time in relation to their relative military capacity. Using archival documents and interviews, I also show how the pre-existing political economy constrains governance options if insurgents do control resources. This can lead to a rebel resource curse and weak institutions similar to what befalls state regimes.